Maximization of fitness by phenological and phenotypic plasticity in range expanding rabbitfishes (Siganidae). Issue 8 (17th May 2022) - Zarco‐Perello, Salvador; Fairclough, David; Dowling, Chris; DiBattista, Joey; Austin, Rachel; Wernberg, Thomas; Taylor, Brett
Abstract: Global warming is modifying the phenology, life‐history traits and biogeography of species around the world. Evidence of these effects have increased over recent decades; however, we still have a poor understanding of the possible outcomes of their interplay across global climatic gradients, hindering our ability to accurately predict the consequences of climate change in populations and ecosystems. We examined the effect that changes in biogeography can have on the life‐history traits of two of the most successful range‐extending fish species in the world: the tropical rabbitfishes Siganus fuscescens and Siganus rivulatus . Both species have established abundant populations at higher latitudes in the northern and southern hemispheres and have been identified as important ecological engineers with the potential to alter the community structure of seaweed forests (Laminariales and Fucales) in temperate regions. Life‐history trait information from across their global distribution was compiled from the published literature and meta‐analyses were conducted to assess changes in (i) the onset and duration of reproductive periods, (ii) size at maturity, (iii) fecundity, (iv) growth rates, (v) maximum body sizes and (vi) longevity in populations at the leading edge of range expansion in relation to sea surface temperature and primary productivity (a common proxy for nutritional resource levels). Populations at highest latitudes had shortened their reproductive periods and reduced growth rates, taking longer to reach sexual maturity and maximum sizes, but compensated this with higher fecundity per length class and longer lifespans than populations in warmer environments. Low primary productivity and temperature in the Mediterranean Sea resulted in lower growth rates and body sizes for S. rivulatus, but also lower length at maturity, increasing life‐time reproductive output. The results suggest that plasticity in the phenology and life‐history traits of range‐expanding species would be important to enhance their fitness in high latitude environments, facilitating their persistence and possible further poleward expansions. Quantifying the magnitude and direction of these responses can improve our understanding and ability to forecast species redistributions and its repercussions in the functioning of temperate ecosystems. Abstract : Range‐expansions can produce disparate life‐history changes according to specific new environmental conditions. However, different strategies converge in the maximization of fitness through adaptations in reproduction, growth and longevity. This is an important consideration when predicting species redistributions and consequences for receptive ecosystems.